Responsive Feeding Management of Mothers with Picky Eater Incidents in Children Aged 1 Year To 3 Years - Sunanto, Sunanto; Handayani, Erna; Imran, Suryadi (West Science Interdisciplinary Studies, 2024)
Responsive Bolstering is the capacity of moms to effectively give nourishment in which there's an demeanor in nourishing agreeing to the age of the child, can empower children to eat without constraint, can give a safe environment within the process of children learning to eat conjointly how to utilize positive intelligent when children eat. The estimation of picky eaters was carried out utilizing the Child Eating Conduct Survey (CEBQ) which was received from the children's eating behavior survey. The reason of the consider was to decide the relationship between maternal responsive bolstering and the rate of picky eaters in children matured 1 year to 3 a long time in Sentul Probolinggo Town. The comes about of the ponder conducted on 35 respondents gotten the most noteworthy esteem of Responsive Nourishing Mother, to be specific 21 respondents (60%) with the category of Continuously and the comes about of picky eating given to children gotten the most noteworthy esteem, specifically 22 respondents (62.9%) with the category of bolstering more than 1 x a day Information investigation utilizing the spearman correlation test appeared that there was a relationship Responsive Nourishing of Moms with Picky Eater Rate in children matured 1 to 3 a long time in Sentul Probo Departement of Nursing, linggo town with a P esteem of 0.000 < 0.05, at that point Ha is acknowledged. Children's eating propensities can be affected by the part of guardians or caregivers with children through child rearing in bolstering.